Quantitative Assessment of Pain Threshold Induced by a Single-Pulse Transcranial Magnetic Stimulation - Tani, Keisuke; Hirata, Akimasa; Tanaka, Satoshi (Frontiers in Neuroscience, 2020)
Transcranial magnetic stimulation (TMS) is commonly used in basic research to evaluate human brain function. Although scalp pain is a side effect, no studies have quantitatively assessed the TMS intensity threshold for inducing pain and whether sensitivity to TMS-induced pain differs between sexes. In the present study, we measured pain thresholds when single-pulse TMS was applied over either Broca’s area (BA) or left primary motor cortex (M1), and compared these thresholds with the motor threshold (MT) for inducing motor evoked potentials (MEPs) through M1 stimulation. Additionally, we compared the pain thresholds for BA and M1 between males and females. We found that pain thresholds for both sites were significantly lower than the MTs. Furthermore, the pain threshold for BA was much lower than that for M1. No significant difference was observed between sexes. The results suggest that TMS at an intensity equivalent to MTs, which is often used in experimental or clinical studies, causes slight scalp pain. Experimental designs using TMS to evaluate functional relationships between brain and behavior should consider scalp pain and reduce its likelihood as much as possible.